2017
DOI: 10.1515/med-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of meningioma growth in pregnancy

Abstract: AbstractMeningioma is among the most frequent brain tumours predominantly affecting elderly women. Epidemiological studies have shown that at the age of fertility the incidence is relatively low. The biological behaviour of meningioma in pregnancy is different from other meningiomas. The possible explanation is rooted in the complex physiological changes and hormonal differences during pregnancy. The increased meningioma growth observed in pregnancy is presumably the result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 37 publications
1
64
0
Order By: Relevance
“…In this study, the most common histological type of tumor was meningioma (19.5%, eight cases). This may be related to the fact that meningiomas are known to express progesterone receptors, which lead to increased symptom severity during pregnancy [41]. The histological types of brain tumors are diverse [38], and in this study, we found a great variety of histological types not necessarily specific to pregnancy, which is in accordance with previous reports [37,42].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the most common histological type of tumor was meningioma (19.5%, eight cases). This may be related to the fact that meningiomas are known to express progesterone receptors, which lead to increased symptom severity during pregnancy [41]. The histological types of brain tumors are diverse [38], and in this study, we found a great variety of histological types not necessarily specific to pregnancy, which is in accordance with previous reports [37,42].…”
Section: Discussionsupporting
confidence: 92%
“…Although a typically slow-growing tumour, a meningioma can have accelerated growth in pregnancy because of increasing oestrogen and progesterone levels and vascular endothelial growth factors. 19 The incidence of meningiomas during pregnancy is estimated at 5.6 cases in 100,000 pregnant women. 20 A pre-existing sphenoid bone meningioma near the optic canal can result in compressive optic neuropathy.…”
Section: Meningiomamentioning
confidence: 99%
“…[21][22][23][24] On the other hand, vascular changes, possibly related to the expression of VEGF, have been shown to be an additional causative mechanism for growth of meningiomas during pregnancy. 25,26 Also, the expression of other growth factor receptors, such as FGF-R and PDGF-Rβ, may be involved. 27 For orbital schwannoma it is unclear what may cause excessive growth during pregnancy and little is known about receptor expression of these tumors.…”
Section: Discussionmentioning
confidence: 99%